The Power of And Responsible Business Without Trade-Offs - Freeman, R. Edward 1951-; Martin, Kirsten; Parmar, Bidhan L. (Columbia University Press, 2020)
The idea that business is only about the money doesn’t hold true in the twenty-first century, when companies around the world are giving up traditional distinctions in order to succeed. Yet our expectations for businesses remain under the sway of an outdated worldview that emphasizes profits for shareholders above all else.The Power of And offers a new narrative about the nature of business, revealing the focus on responsibility and ethics that unites today’s most influential ideas and companies. R. Edward Freeman, Kirsten E. Martin, and Bidhan L. Parmar detail an emerging business model built on five key concepts: prioritizing purpose as well as profits; creating value for stakeholders as well as shareholders; seeing business as embedded in society as well as markets; recognizing people’s full humanity as well as their economic interests; and integrating business and ethics into a more holistic model. Drawing on examples across companies, industries, and countries, they show that these values support persevering in hard times and prospering over the long term. Real-world success stories disprove the conventional wisdom that there are unavoidable trade-offs between acting ethically and succeeding financially. The Power of And presents a conceptual revolution about what it means for business to be responsible, providing a new story for us to tell in order to help all kinds of companies thrive